ChemInform Abstract: Two Ternary Mixed‐Anion Chlorides with Divalent Europium: Eu2H3Cl and Eu7F12Cl2. Issue 32 (24th July 2014) - Reckeweg, Olaf; DiSalvo, Francis J.; Wolf, Sarah; Schleid, Thomas
Abstract: Eu2 H3 Cl (I) and Eu7 F12 Cl2 (II) are obtained by solid‐state reactions of Eu, NaH, NaCl, and Na (2:4:1:2 molar ratio) or Eu, EuCl3, and LiF (1:1:4 molar ratio), resp.